Incidence of pressure ulcers in intensive care units and direct costs of treatment: Evidence from Iran. Issue 2 (May 2019) - Zarei, Ehsan; Madarshahian, Elmira; Nikkhah, Adeleh; Khodakarim, Soheila
Abstract: Background and objective: Pressure ulcer (PU) is one of the important and frequent complications of hospitalization, associated with high treatment costs. The present study was conducted to determine the incidence of PU and its direct treatment costs for patients in intensive care unit (ICU) in Iran. Material and methods: In this retrospective study, medical records of 643 discharged patients from ICU of two selected hospitals were examined. The demographic and clinical data of all patients and data of resources and services usage for patients with PU were extracted through their records. Data analysis was done using logistic regression tests in SPSS 22 software. The cost of PU treatment was calculated for each grade of ulcer. Results: The findings showed that 8.9% of patients developed PU during their stay in ICU. Muscular paralysis (OR = 5.1), length of stay in ICU (OR = 4.0), diabetes (OR = 3.5) age (OR = 2.9), smoking (OR = 2.1) and trauma (OR = 1.4) were the most important risk factors of PU. The average cost of PU treatment varied from USD 12 for grade I PU to USD 66 834 for grade IV PUs. The total treatment costs for all studied patients with PU was estimated at USD 519 991. Conclusion: The cost of PU treatment is significant. Since the preventive measures are more cost-effective than therapeutic measures, therefore, effective preventive interventions are recommended. Highlights: The findings showed that 8.9% of patients developed PU during their stay in ICU. Length of stay, patient's age, smoking, muscular paralysis, trauma and diabetes were the most important risk factors of PU. The average cost of PU treatment varied from USD 12 for grade I PU to USD 66 834 for grade IV PUs. The total treatment costs for all studied patients with PU was estimated at USD 519 991.